Modern Semantics in Arabic Linguistics: Structural-Pragmatic Approaches and Synonymic Differentiation (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the developmental stages and main directions of modern semantics within the scope of Arabic linguistics, with a particular focus on the analysis of synonymous units in the context of structural and pragmatic approaches. The theoretical foundations of lexical, phonetic, morphological, syntactic, contextual, and social semantics are systematically substantiated by examples from the Arabic language. The study investigates how Arabic synonymous units differ at paradigmatic and syntagmatic levels based on linguistic criteria. This study is the first to propose an integrative semantic model that combines structural and pragmatic factors, comprising denotative, connotative, and pragmatic components. Based on this approach, context-specific semantic differences among synonyms are thoroughly analyzed, and their functional loads are identified. The theoretical model proposed is considered a potentially effective descriptive tool in applied linguistics, particularly in Arabic lexicography, translation theory, and computational linguistics.